2021
DOI: 10.3390/ijerph18147557
|View full text |Cite
|
Sign up to set email alerts
|

How the Number of Players and Floaters’ Positioning Changes the Offensive Performance during Futsal Small-Sided and Conditioned Games

Abstract: This study aims to analyse the effects of floater positioning within futsal Gk + 3vs3 + Gk and Gk + 2vs2 + Gk small-sided and conditioned games (SSCG) on youth offensive performance on an action per minute per player basis. Three experimental conditions were carried out through the manipulation of floater positioning: floaters off (FO), final line floaters (FLF) and lateral floaters (LF). Thirty male futsal players (U19 age category) participated in the study and played once within each situation in a random o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For this purpose, coaches may change the boundary conditions during SSGs. For example, Práxedes, Moreno, Gil-Arias, Claver, and Del Villar [36], Machado, Barreira, Teoldo, Travassos, Júnior, Santos, and Scaglia [56], and Pizarro et al [57] revealed improvements in performances in passing DM and execution in the low-difficulty/DM scenarios (i.e., numerically unbalanced tasks or during SSGs with a lower number of players). Apart from variations in the number of players during SSGs, coaches often vary the level of task DM by adopting more prescriptive and repetitive passes or tasks without opposition [7,40].…”
Section: Comparing the Interventions' Acute Effects Between Groups (B...mentioning
confidence: 99%
“…For this purpose, coaches may change the boundary conditions during SSGs. For example, Práxedes, Moreno, Gil-Arias, Claver, and Del Villar [36], Machado, Barreira, Teoldo, Travassos, Júnior, Santos, and Scaglia [56], and Pizarro et al [57] revealed improvements in performances in passing DM and execution in the low-difficulty/DM scenarios (i.e., numerically unbalanced tasks or during SSGs with a lower number of players). Apart from variations in the number of players during SSGs, coaches often vary the level of task DM by adopting more prescriptive and repetitive passes or tasks without opposition [7,40].…”
Section: Comparing the Interventions' Acute Effects Between Groups (B...mentioning
confidence: 99%
“…Understanding and quantifying external and internal load demands in futsal provides important information for coaches and may be useful in designing appropriate training programs ( 17 ). For instance, Pizarro et al ( 18 ) analyzed the effects of number of players and floater position on offensive performance during small-sided games (SSGs) in U19 male futsal players. The study revealed notable distinctions between 2 vs. 2 and 3 vs. 3, highlighting the impact of player numbers on team tactical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Futsal is an indoor sport played by five players on each team and ruled internationally by FIFA; according to this organization, there are approximately 12 million players worldwide. Despite being a more dynamic sport, it is considered a variant of football due to its greater intensity [1], requiring athletes to quickly adapt their actions during the game to their team and opponents in less time and space [2]. This sport requires movement in various directions, as well as accelerations, decelerations, and intense direction changes, with an average of around 670 of these actions being observed during the match [3].…”
Section: Introductionmentioning
confidence: 99%